UJI LAJU KAPILARITAS DAN PEMBAKARAN MINYAK JARAK MENGGUNAKAN SUMBU KOMPOR SEBAGAI ACUAN DALAM MENDESAIN KOMPOR MINYAK JARAK - Amona A Situmorang; Edward Saleh; R. Mursidi Mursidi (Universitas Sriwijaya, 2012)
The objective of this research was to study the capillarity and the firing rate of castor oil. The research used group randomized design with two factors (A and B) and two replications. Factor A was fence castor oil temperature (500C, 600C, 700C) and factor B was wick stove diameter (10 mm, 5 mm). The observed data were include firing rate (mL/s), flash point (0C), viscosity (cst), surface tension (N/m), porosity (%) and the rate capillarity (mL/s). The result showed that temperature, diameter of wick stove and their interaction have a significant effect on capillarity and firing rate. The combination of temperature 700 C and 5 mm wick stove diameter (D2T3) had the best characteristic with the firing rate of 0.0226 mL/s and the capilarity of 0.0101 mL/s. Increase of temperature on castor oil will decrease value of the viscosity of castor oil stiffness.Keywords : Rate capilarity, Firing rate, Stove wick, castor oil.